(untitled) (Research, Society and Development, 2022)
Introduction: The estimate of new cases of cancer by the National Cancer Institute (INCA), in 2020, was more than 620 thousand cases and the important association between neoplasms and lifestyle should be considered. Kefir has been gaining ground due to its properties, including its anti-cancer action. Objective: To evaluate the anticarcinogenic effect of kefir on Drosophila melanogaster cells. Methodology: Kefir was tested by means of the Epithelial Tumor Test (ETT) in D. melanogaster. Females of the wts lineage and males of the mwh lineage were crossed. The offspring larvae were treated with three concentrations of kefir: 1.25mg/mL; 2.5mg/mL and 5.0mg/mL alone and in association with the chemotherapy drug doxorubicin (DXR). Results and discussion: Kefir was not carcinogenic at any of the concentrations tested and had an anticarcinogenic effect at the three concentrations tested. Final considerations: The study suggests a beneficial effect of kefir in cancer prevention and treatment.